Early Medieval Genoa - Balzaretti, Ross (Brill, 2018)
The earliest coherent written documentation for Genoa in the early medieval period is from the latter part of the tenth century. Charters documenting the property transactions of several local churches (notably San Siro and Santo Stefano) reveal that the bishop and his clergy had property rights at the extremities of costal Liguria and in the interior. Fifty eight texts have survived between 916 and 1000 Synopsis, A Companion to Medieval Genoa (Brill, 2017) 3 and the first part of this chapter is devoted to their detailed analysis. This number is rather fewer than for comparable Italian urban centres and that fact needs to be explained. Nor has a substantial local historical narrative survived until the twelfth century, albeit more typical of wider Italian patterns.